Improving the Efficiency of a Nuclear Power Plant Using a Thermoelectric Cogeneration System - Rauf Terzi; Erol Kurt (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
The efficiencies of nuclear power plants are rather poor having the ratio %30 by using the conventional energy/exergy tools. According to that information, large amount of energy is wasted during condensation and thrown out to the environment. Thermoelectric generator (TEG) system has a potential to be used as a heat exchanging technology to produce power with a relatively low efficiency (about 5%) and it can transform the temperature difference into electricity and generate clean electrical energy. In the present study, we offer a novel system to recover the waste heat from a VVER-1000 nuclear power plant. The heat transfer of the TEG is analyzed numerically with respect to the various temperature ranges and constant mass flow rate of the exhaust steam entering the system. In the analyses, different hot temperature ranges (35ºC, 45ºC and 55ºC) and a constant cold temperature (i.e. 18ºC) are used for a HZ-20 thermoelectric module and it has been proven that the designed TEG can produce the maximum output power of 76,956 MW for a temperature difference ∆T=37 and the conversion efficiency of 3.854% sits. The TEG is designed for the condenser of a 1000 MW nuclear power plant. It's shown that about 2.0% increasing in the power plant efficiency is expected by using the selected thermoelectric generator in the condensation cycle.Article History: Received: July 15th 2017; Received: October 17th 2017; Accepted: February 13rd 2018; Available onlineHow to Cite This Article: Terzi, R. and Kurt, E. (2018), Improving the efficiency of a nuclear power plant using a thermoelectric cogeneration system, Int. Journal of Renewable Energy Development, 7(1), 77-84.https://doi.org/10.14710/ijred.7.1.77-84